Symmetry Extensions and Their Physical Reasons in the Kinetic and Hydrodynamic Plasma Models - Taranov, V.B. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
Characteristic examples of continuous symmetries in hydrodynamic plasma theory (partial differential equations) and in kinetic Vlasov-Maxwell models (integro-differential equations) are considered. Possible symmetry extensions conditional and extended symmetries are discussed. Physical reasons for these symmetry extensions are clarified.